The Genesis of the Idea ‘Dutch Written Literature’ in Bohemia - Engelbrecht, Wilken (Werkwinkel, 2016)
Since mid-19th century Dutch and Flemish literature has often been translated into Central European languages. We find authors like Conscience, Multatuli or Heijermans almost everywhere, often with the same works. Until the late 19th century translations were often made via German. Czech had a special position. Though there is not that much translated into this language as into German, until World War II Czech was the language into which was translated more than into other Central European languages. Until the 20s many translators were writers themselves. This gives rise to questions such as how the choice was made, what is the position of a particular author or his work within translated literature? How was Dutch literature defined? In this paper, we give a look how the choice was made, at the position of translators of Dutch literature in the late 19th and early 20th century in the Czech literary field, the position of Dutch in their work and how this literature was received in translation.